Decomposing the Wage Losses of Displaced Workers: The Role of the Reallocation of Workers into Firms and Job Titles - Pedro Raposo; Pedro Portugal; Anabela Carneiro (Institute for the Study of Labor (IZA), 2015)
Using an unusually rich matched employer-employee-job title data set for Portugal, this paper evaluates the sources of wage losses of workers displaced due to firm closure based on the comparison of workers' wages differentials before and after displacement. Potential wage losses of displaced workers can be related to firm, job title, and match heterogeneity in the pre- and post-displacement jobs. In this vein, we estimate a three-way high-dimensional fixed effects regression model that enables us to decompose the sources of the wage losses into the contribution of firm, job title, and match fixed effects. The worker-firm match plays a very sizable role. We found that the allocation of workers into poorer matches accounts for 38 percent of the total average wage loss. Sorting among firms accounts for 36 percent. Job downgrading also plays a significant role in explaining the wage loss of displaced workers, accounting for the remaining 26 percent.
Keywords: J31; J63; J65; E24; 330; match effects; job title; high-dimensional fixed effects; displaced; wage losses